Ranking of general circulation models for Surat City by using a hybrid approach. Issue 10 (3rd October 2022) - Sharma, Arpit; Kale, Ganesh D.
Abstract: Climate change is expected to worsen flood risks by increasing precipitation in and around Surat City. Thus, to study the effect of climate change on Surat City's stormwater drainage network, ranking of general circulation models (GCMs) and generation of future annual maximum rainfall series is needed, which has not been performed by any reviewed study and is performed in the present study by using a hybrid approach. The 'hybrid approach' refers to the combination of past performance approach used for ranking of GCMs and envelope approach based on future climate projections. To rank 21 GCMs belonging to Coupled Model Intercomparison Project Phase 5, a past performance approach is employed by using four performance indicators, which are evaluated on the basis of Surat's simulated and observed monthly rainfall data corresponding to the period 1969–2005. By using an entropy method, weights are assigned to different performance indicators and then ranking of GCMs is performed by employing the TOPSIS method. The top five ranked GCMs are used to generate future annual maximum rainfall series by employing the Reliability Ensemble Averaging method corresponding to Representative Concentration Pathways scenarios 4.5 and 8.5. This study will be helpful for future climate and hydrologic studies to be performed in the study area. HIGHLIGHTS: A hybrid approach is applied in the present study to generate future annual maximum rainfall series for Surat City corresponding to two climate change scenarios. The future annual maximum rainfall series generated in this study will be useful for various climatic and hydrologic studies to be performed in the study area. Graphical Abstract